Agency Costs, Voting Divergence, and Corporate Governance: A Qualitative Synthesis of Dual-Class Stock and Sunset Clause Mechanisms - Benardi; Eri Kusnanto (International Journal of Business Law, Business Ethic, Business Comunication & Green Economics, 2026)
This qualitative literature review synthesizes contemporary research on how dual-class share structures shape agency costs, voting divergence, and corporate governance outcomes. The review finds that disproportionate voting rights increase managerial entrenchment risks and weaken shareholder oversight, thereby amplifying agency costs across diverse institutional settings. However, governance safeguards particularly time bound and event-based sunset clauses emerge as effective mechanisms for moderating the long-term risks of control disproportionality. While dual class firms may benefit from strategic insulation that fosters innovation and long-term value creation, the absence of sunset provisions is consistently associated with reduced firm valuation, diminished accountability, and persistent divergence between control and ownership. Overall, this synthesis highlights that dual-class structures are not universally harmful, but their sustainability depends on the presence of robust governance constraints designed to restore alignment over time.